Implementing Guide Imagery for Elderly with Diabetes Mellitus Post Covid-19 who Experiencing Respiratory Disorders - Pajriyah Pajriyah (Indonesian Journal of Community Development, 2022)
The success of health development in Indonesia has had an impact, among others, on increasing the life expectancy of the elderly. One of the health problems that often occur in the elderly is diabetes mellitus. Various complications from diabetes mellitus can very easily occur, especially during the current Covid-19 pandemic. Preliminary studies conducted by WHO on the relationship between diabetes and Covid-19 showed that around 25 percent of Covid-19 patient s in hospitals with poor conditions had diabetes. With advanced age, of course it is very risky if you depend only on drugs, therefore non-pharmacological therapy is needed, one of which is relaxation techniques. The National Safety Council says guided imagery is a distraction technique that can be used to reduce stress and increase feelings of calm and peace and is a sedative for difficult situations in life. Purpose: to determine the effectiveness of guided imagery therapy in the elderly with post-covid-19 diabetes mellitus who experience respiratory tract disorders. Method: case study conducted by observation. Results: After 7 days, 2 hours after the intervention, the authors measured blood pressure, checked SPO2 and calculated the respiratory system back to Mr.A. The results obtained were 120/80 mmHg, SPO2 95% and respiration 20x/minute. Patient said he was not short of breath, Patient looks no longer limp pale like the first day the assessment was carried out. Conclusion: there is an effect of guided imagery therapy in the elderly with post-covid-19 diabetes mellitus who experience respiratory tract disorders